2020
DOI: 10.21577/0103-5053.20190200
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Reduced Graphene Oxide on Gold Electrodes from Recordable CDs: Characterization and Potential Sensing Applications

Abstract: This work presents the development and characterization of a new chemically modified electrode exploiting recordable Au-rewritable compact discs (AuCDs) as substrate for drop casting of a chemically-reduced graphene-oxide slurry focusing on simple and low-cost electrochemical sensors. Increase in electrochemical responses in cyclic voltammetric and amperometric measurements were achieved using the proposed sensor. Both scanning electron microscopy and atomic force microscopy data showed increase in rugosity (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…22−24 It has been shown that in carbonous materials, the edge plane is extremely more reactive than the basal plane and facilitates the rate of HET. The basal plane contains carbon with sp 2 hybridization; it is flat with low defect density, while the edge plane contains sp 3 sites, functional groups, dangling bonds, and defects due to the abrupt lattice termination. The electrochemical activity of the basal plane is very low and depends on the history and the number of defects on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22−24 It has been shown that in carbonous materials, the edge plane is extremely more reactive than the basal plane and facilitates the rate of HET. The basal plane contains carbon with sp 2 hybridization; it is flat with low defect density, while the edge plane contains sp 3 sites, functional groups, dangling bonds, and defects due to the abrupt lattice termination. The electrochemical activity of the basal plane is very low and depends on the history and the number of defects on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonous materials have been extensively used for the fabrication of various electrodes/sensors/biosensors compared to other materials because of their appropriate chemical inertness, wide potential window, great mechanical resistance, flexible surface modification, and cost-effectiveness. It is well known that the rate of heterogeneous electron transfer (HET) at the interface of carbonous electrode and electrolyte solution mainly depends on defect density, type of defect, and morphology (grain boundaries) of the carbonous materials. These factors also play a remarkable role in the selectivity and performance of the redox reactions, electrocatalytic reactions, sensing, etc. The difference in the rate of HET in many studies has been attributed to the difference in electrode morphology as the main factor, which can be easily explored and compared .…”
Section: Introductionmentioning
confidence: 99%
“…O processo de modificação por adsorção vem sendo bastante utilizado para incorporar dispersões de rGO em diferentes substratos eletroquímicos. Em grande parte dos trabalhos reportados na literatura, são observadas modificações estáveis com baixa dessorção do modificador, possibilitando obter uma boa reprodutibilidade do sinal analítico durante as análises (GAN et al, 2014;SILVA et al, 2020;VASCONCELOS et al, 2020). O método drop casting é o mais empregado para este propósito, em razão da simplicidade e baixo custo.…”
Section: Eletrodos Modificados Com Grafenounclassified